Theoretical investigations of α,α,α-trifluoro-3, -p and o-nitrotoluene by means of density functional theory - Yıldırım, Gürcan; Şenol, Sevim Demirözü; Doğruer, Musa; Öztürk, Özgür; Şenol, Abdulkadir; Taşçı, A. T.; Terzioğlu, Cabir (Elsevier BV, 2012)
This study reports the optimized molecular structures, vibrational frequencies including Infrared intensities and Raman activities, corresponding vibrational assignments, (1)H and (13)C NMR chemical shifts, the magnitudes of the JCH and JCC coupling constants, Ultraviolet-visible (UV-vis) spectra, thermodynamic properties and atomic charges of the title compounds, α,α,α-trifluoro-3, -p and o-nitrotoluene, in the ground state by means of the density functional theory (DFT) with the standard B3LYP/6-311++G(d,p) method and basis set combination for the first time. Theoretical vibrational spectra were interpreted by normal coordinate analysis based on scaled density functional force field. The results show that the vibrational frequencies and chemical shifts calculated were obtained to be in good agreement with the experimental data. Based on the comparison between experimental results and theoretical data, the calculation level chosen is powerful approach for understanding the identification of all the molecules studied. In addition, not only were frontier molecular orbitals (HOMO and LUMO), molecular electrostatic potential (MEP) and electrostatic potential (ESP) simulated but also the dipole moment, softness, electronegativity, chemical hardness, electrophilicity index, transition state and energy band gap values were predicted. According to the investigations, all compounds were found to be useful to bond metallically and interact intermolecularly; however, the thermodynamic properties confirm that the α,α,α-trifluoro-p-nitrotoluene was more reactive and more polar than the others.
Keywords: Models, Molecular; B3LYP; Magnetic Resonance Spectroscopy; Halogenation; Static Electricity; MEP; Alpha,alpha,alpha-Trifluoro-3, -p and o-nitrotoluene; Quantum Theory; Spectrophotometry, Ultraviolet; ESP; Toluene; 7. Clean energy